Method of alkali solution concentration at electrochemical processing of eluates containing sodium salts - Трус, Інна Миколаївна; Гомеля, Микола Дмитрович; Радовенчик, Ярослав Вячеславович (Eastern-European Journal of Enterprise Technologies, 2013)
The paper gives the results of electrochemical concentration of alkali solutions, produced by electrolysis of sodium chloride or sodium sulfate. It was found that using two-chambered electrolyzer, the interelectrode space of which is separated by MK-40 membrane, allows increasing alkali concentration from 0.1-1.0D to 13D. It is shown that with anolyte alkalinity>0.1D alkali concentration in the anode region has little effect on electrolysis efficiency. Concentration is effective with alkaline solution in the anode region>0.1D. As a whole, efficiency depends on both alkalinity in the cathode and anode regions and current density. It is proved that increasing anodic current density from 10 to 20 A/dm2 leads to increasing not only the speed of alkali concentration in the cathode region, but also alkali current efficiency. Further increase in current density is irrelevant because there is no increase in speed, but the solution heating. It was found that partial reduction of alkali concentration in the cathode region is conditioned by reverse-osmotic water transfer.